Correlation Hemodialysis Intensity with Anxiety in Chronic Kidney Failure Patients - Nur Soemah, Eka; Adiwibowo, Galih (Kirana Publisher (KNPub), 2022)
This study looked at the link between hemodialysis intensity and anxiety in individuals with chronic renal failure who were receiving hemodialysis. A correlation analysis is the method of study. The population for this study consisted of 80 respondents, and 35 samples were taken using consecutive sampling methods. The Chi-Square test was used for data analysis in this study using SPSS for Windows version 25.0. The results of the research and data analysis can be used to draw the conclusion that there is a correlation between the intensity of hemodialysis and anxiety levels in patients with chronic renal failure undergoing hemodialysis, as determined by the Chi-Square test calculation of sig value of 0.020 0.05. The research was conducted on 35 respondents. It was determined that among patients with chronic renal failure receiving hemodialysis, there was a link between the intensity of hemodialysis and the degree of anxiety. The patient starts to adapt well and the degree of anxiety starts to reduce following continued therapy, which is expected to help the family support and encourage the patient.